Rethinking Criminal Responsibility for Poor Offenders: Choice, Monstrosity, and the Logic of Practice - Sylvestre, Marie-Eve (McGill Law Journal / Revue de droit de McGill, 2010)
In theory and in discourse, Canadian criminal law insists on the importance of free will, choice, and difference in order to hold someone criminally responsible and to legitimize punishment. Yet legal doctrine is constructed and applied in a very technical and descriptive manner that usually casts aside practical considerations, proceeds on utilitarian grounds, and simplifies what it means to be free, rational, and different. Recent proposals to strengthen or to eliminate the retributive model (e.g., to include in the analysis considerations such as socio-economic disparities and power differential or to definitely shift the discourse toward utilitarian considerations) still rely on assumptions about agency, liberty, and equality that are grounded in contested sociological evidence. As a result, their capacity to promote concrete reform is limited.In this paper, the author draws from the works of Bourdieu and other praxis theorists and argues that their research could shed new light on our understanding of choice and difference—two essential components in the assessment of responsibility. The author concludes by showing what criminal law theory could look like, especially in the case of poor offenders, if reformers were to consider such sociological evidence.